Multi-agent architectures for Fault Tolerant networked control systems - Mendes, Mário J. G. C. (2019)
In large-scale complex networked control systems (NCS) the design of Fault Tolerant Control (FTC) systems is a very difficult task due to the large number of sensors and actuators spatially distributed and networked connected. Any solution given to this problem must take into account that practitioners prefer rather simplistic solutions since in practice, simple and verifiable principles always win the competition versus complex solutions that are usually characterized by instability, unpredictable behaviour and large computational burden. This paper presents and discusses different multiagent architectures for Fault Tolerant Networked Control Systems (FTNCS). The chosen multi-agent approach to FTNCS is presented and it’s done using simple and verifiable principles coming mainly from a decentralized design based on causal modelling partitioning of the NCS and distributed computing using multi-agent paradigm, allowing the use of well established FTC methodologies or new ones developed taking into account the NCS specificities.